Environmental turbulence and the role of business functions in the manufacturing strategy debate: The case of UK-based SMEs and the Great Recession. (July 2019) - Sainidis, Eustathios; Robson, Andrew; Heron, Graeme
This study provides an empirical assessment of the United Kingdom (UK) manufacturing small and medium-sized enterprises (MSMEs) sector, exploring the impact of environmental turbulence specific to the post–Great Recession (2008) era on changes to the way manufacturing strategy is formulated and implemented. The study identifies changes to the frequency, fluidity, formality and focus of manufacturing strategy review and how the various business functions play a changing role in contributing to this strategic process. A mixed-methods research approach is applied, incorporating a survey of 104 UK-based manufacturing SMEs supported by 17 in-depth interviews with senior managers. The research uses a parallel mixed analysis of the two data sources, thereby offering an alternative to the mono-quantitative approaches to manufacturing research that have dominated. The findings show that during, and emerging from, the post–Great Recession environment, the majority of manufacturing SMEs employ a fluid, highly frequent approach to manufacturing strategy review with increasing contributions from their marketing, sales and finance business functions driven predominantly by function-specific response to changes in the external environment, although internal drivers sill influence high-level strategy, finance and human resources. The implications of the study to theory, practice and general management suggest that the MSME sector is dominated by organizations experiencing continual impact from the external environment.